Borders, Bodies and Narratives of Crisis in Europe - Lagios, Thanasis (Springer International Publishing, 2018)
This book critically discusses two crises that shape our present: migration crisis and 2007-2008 crisis. The first part raises several questions regarding migration, borders, labour, humanitarianism and biopolitics; the second part focuses on the false dilemma between an interpretation of contemporary crisis in the West as capitalist or humanist. Thanasis Lagios is Teaching Assistant at the University of Athens, Greece. Vasia Lekka is Adjunct Academic Staff at the Hellenic Open University, Greece. Grigoris Panoutsopoulos is Researcher at the University of Athens, Greece.